Impact of Continuous Glucose Monitoring on Hemoglobin A1c and Height Trends in Latin American Children with Type 1 Diabetes Onset over 3 Years: A Multicenter Study - Valeria Hirschler, MD; Claudia Molinari, Msc; Claudio D. Gonzalez, MD; Maria Eugenia Andres; Angela Figueroa Sobrero; Victoria Femenia; Guadalupe Pietropaolo; Maria L. Major; Edit Scaiola; Sandra Mazzetti; Patricia Pasayo; Amanda J. Benitez; et al. (Journal of Pediatrics: Clinical Practice)
Objective: To evaluate changes in hemoglobin A1c (HbA1c) levels and z-height over 3 years based on continuous glucose monitoring (CGM) usage among children with new-onset type 1 diabetes (T1DM) from various Latin American centers. Study design: Data on z-height, CGM access, and HbA1c (%) were collected for Latin American children aged 6 months to 18 years with T1DM onset from 19 centers in a retrospective analysis of medical records, from 2020 to 2023. A 2-way ANOVA method with repeated measures and multiple regression analyses were performed. Results: We included 433 children (46.0% female) aged 8.7 ± 3.7 years; 199 (45.9%) used CGM. The mean HbA1c was significantly lower in years 1, 2, and 3 than at baseline in children with CGM, but not those without CGM. The z-height decreased significantly with the years in both groups. However, the CGM users showed a significantly greater height in years 2 and 3 than the nonusers. Multiple linear regression analysis showed that CGM users exhibited a significantly lower incremental area under the curve (AUC) for HbA1c during follow-up than nonusers. Furthermore, a lower incremental AUC for HbA1c was associated with a smaller decremental AUC for z-height (R2 = 0.19). Multiple logistic regression analysis revealed that children with CGM were 80% more likely (OR, 0.22; 95% CI, 0.1-0.6) to achieve an HbA1c of <7% in the third year of follow-up. Conclusions: This study reveals a significant association between CGM use and lower HbA1c from the onset of T1DM over a 3-year follow-up in Latin American children. Further prospective studies should be performed to confirm this finding.